1992
DOI: 10.1002/1097-0142(19921215)70:12<2942::aid-cncr2820701235>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of cancer in papua new guinea. An analysis based on the cancer registry 1979-1988

Abstract: Malignant tumors registered with the Tumour Registry of Papua New Guinea (PNG) from 1958–1988 were analyzed with emphasis on the variation of incidence with time and different regions. Cancer incidence was generally low in PNG. During this period, carcinoma of oral cavity, cervix, breast, and skin, hepatoma, and lymphoma were the most common types of malignant lesions detected. The incidence of carcinoma of the oral cavity has increased. Currently, it is more common in the Highlands region and is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…As with all forms of oral cancer it is noted that the vast majority of data comes from the Western world where the incidence of mouth cancer is generally quite low. With the exception of the well-established registries in India itself (Gupta and Nandakumar, 1999), there is a paucity of reliable population-based data from most developing countries where the rates of this form of cancer are known to be elevated, notably Papua New Guinea and the islands of Melanesia (Taylor et al, 1983;Martin et al, 1992).…”
Section: Oral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As with all forms of oral cancer it is noted that the vast majority of data comes from the Western world where the incidence of mouth cancer is generally quite low. With the exception of the well-established registries in India itself (Gupta and Nandakumar, 1999), there is a paucity of reliable population-based data from most developing countries where the rates of this form of cancer are known to be elevated, notably Papua New Guinea and the islands of Melanesia (Taylor et al, 1983;Martin et al, 1992).…”
Section: Oral Diseasesmentioning
confidence: 99%
“…While it is generally known that intraoral cancer rates are high in other parts of the Oceania, particularly Papua New Guinea and the islands of Melanesia (Taylor et al, 1983;Martin et al, 1992), no reliable population-based data for mouth cancer incidence have been published from these regions. The Globocan CDRom (Ferlay et al, 1998) gives an incidence rate of 23.08 per 100 000 per annum for 'oral' cancer (lip, mouth, tongue and oropharynx combined) for Melanesia.…”
Section: Figurementioning
confidence: 99%
“…While it is generally known that intraoral cancer rates are high in other parts of Oceania, particularly Papua New Guinea and the islands of Melanesia (Taylor et al, 1983;Martin et al, 1992), no reliable population-based data specifically for tongue cancer incidence have been published from these regions.…”
Section: Asia (A) Malementioning
confidence: 99%
“…Burkitt’s type lymphoma has its special characteristic features. Although a few studies on malignant lymphomas in Papua New Guinea (PNG) have been reported in the literature, 3 , 4 special attention has not been paid to head and neck lymphomas. The aim of the present article will be to focus on the actual incidence of adult lymphomas in this region; their pathology and pattern of clinical presentation.…”
Section: Introductionmentioning
confidence: 99%